2011
DOI: 10.1088/0957-4484/22/48/485704
|View full text |Cite
|
Sign up to set email alerts
|

Modeling electrical conductivities of nanocomposites with aligned carbon nanotubes

Abstract: We have developed an improved three-dimensional (3D) percolation model to investigate the effect of the alignment of carbon nanotubes (CNTs) on the electrical conductivity of nanocomposites. In this model, both intrinsic and contact resistances are considered, and a new method of resistor network recognition that employs periodically connective paths is developed. This method leads to a reduction in the size effect of the representative cuboid in our Monte Carlo simulations. With this new technique, we were ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
100
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(109 citation statements)
references
References 60 publications
9
100
0
Order By: Relevance
“…CNTs with large persistence length, L p ≥ L. It was experimentally demonstrated that the electrical conductivity parallel to the alignment direction displays a non-monotonic dependence on the degree of CNT alignment, with the highest conductivity observed for slightly aligned nanotubes rather than for isotropic case [153]. Similar results were also obtained in the Monte Carlo simulations of the effect of the alignment of CNTs on percolation and electrical conductivity [154][155][156][157]. These models also predicted that the peak value of the conductivity should occur for partially aligned rather than perfectly aligned CNTs.…”
Section: Electrical Conductivitysupporting
confidence: 68%
See 2 more Smart Citations
“…CNTs with large persistence length, L p ≥ L. It was experimentally demonstrated that the electrical conductivity parallel to the alignment direction displays a non-monotonic dependence on the degree of CNT alignment, with the highest conductivity observed for slightly aligned nanotubes rather than for isotropic case [153]. Similar results were also obtained in the Monte Carlo simulations of the effect of the alignment of CNTs on percolation and electrical conductivity [154][155][156][157]. These models also predicted that the peak value of the conductivity should occur for partially aligned rather than perfectly aligned CNTs.…”
Section: Electrical Conductivitysupporting
confidence: 68%
“…The electrical conductivity of composites doped with CNTs can be limited by tube-tube junction conductivity or own conductivity of CNTs [156,157]. The experiments evidenced that the CNT-CNT junction conductivity is much smaller than the conductivity of the CNT themselves.…”
Section: Electrical Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, it has been reported that neither a fully isotropic distribution nor a complete filler alignment are optimal to achieve the highest conductivity [30,31]. However, Bao et al [32] demonstrated that for very small volume fractions of CNTs, higher conductivities are achieved when the filler alignment is closer to isotropic. Specifically the percolation threshold in bulk systems will be higher for aligned fillers than for randomly oriented ones, primarily due to less effective filler interconnection for uniformly aligned fillers.…”
Section: Electrical Percolation In Hybrid Systemsmentioning
confidence: 99%
“…Li et al [25] conducted Monte Carlo simulations and demonstrated that wavy nanotube networks had lower conductivity than that which included only straight nanotubes. In addition, Du et al [26] and Bao et al [27] investigated alignment effects on the electrical properties of 2D and 3D model, respectively.…”
Section: Introductionmentioning
confidence: 99%